Neuroimaging Pharmacopoeia - Ginat, Daniel Thomas; Small, Juan E.; Schaefer, Pamela Whitney; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book, now in a revised and updated second edition, reviews the imaging-relevant features of selected classes of pharmaceuticals and drugs regarding CNS and head and neck images. The agents discussed belong to classes like Drugs and Alcohol; Contrast Agents; Chemotherapy; Immunotherapy; Antibiotics, Antiviral Agents, and Vaccines; Antiepilectic and Antipsychotic Agents; and Hematologic Agents, each of which is addressed in a separate chapter. The book$1 (Bs closing part addresses agents from various other classes. For each class, concise texts and rich images review and illustrate the mechanism of action. All chapters from the previous edition have been extensively updated, and new chapters on certain pharmaceuticals have been added. Highlighting the implications of these agents for imaging findings, the book offers an excellent resource for neuroradiologists and clinicians alike. .s
PART I: Drugs and Alcohol -- 1. Tobacco -- 2. Alcohol -- 3. Methanol -- 4. Cannabis (Marijuana) -- 5. Synthetic Cannabinoids (spice/K2 preparations) -- 6. Crack and Cocaine -- 7. Amphetamines -- 8. Opioids -- 9. Betel Nuts -- 10. Licorice -- 11. Centella asiatica -- PART II: Contrast Agents -- 12. Iodinated Contrast Agents -- 13. Gadolinium-Based Contrast Agents -- 14. Ferumoxytol -- 15. Pantopaque (Myodil, Iodophenylundecylic Acid) -- 16. Thorium Dioxide (Thorotrast) -- PART III: Chemotherapy -- 17. Temozolamide (Temodar) -- 18. 1,3-Bis(2-Chloroethyl)-1-Nitrosourea (BCNU; Carmustine) Polymer Wafer (Gliadel) -- 19. Methotrexate -- 20. 5-Fluorouracil -- 21. L-Asparaginase (Elspar/Erwinase) -- 22. Calcineurin Inhibitors -- 23. Bromocriptine (Parlodel) and Cabergoline (Dostinex) -- 24. HiDAC (High-Dose Ara-C; Cytarabine; Cytosine Arabinoside; Cytosar-U; Depocyt) -- PART IV: Anti-cancer Immunotherapy -- 25. Ipilimumab (MDX-010, Yervoy) -- 26. Bevacizumab (Avastin) -- 27. Chimeric Antigen Receptor T-Cell Therapy (tisagenlecleucel and axicabtagene ciloleucel) -- PART V: Antiobiotics, Antiviral Agents, and Vaccines -- 28. Metronidazole (Flagyl) -- 29. Iodoform -- 30. Isoniazid -- 31. Highly Active Antiretroviral Therapy (HAART) -- 32. Vaccines -- PART VI: Antiepilectic, Antipsychotic, and General Anesthgetic Agents -- 33. Dilantin (Phenytoin Sodium) -- 34. Valproic Acid (Sodium Valproate, Depakote) -- 35. Vigabatrin (Sabril) -- 36. Lithium -- 37. Neuroleptics -- PART VII: Anesthetic and Sedative Agents -- 38. Barbiturates (Pentobarbital) -- 39. Nitrous Oxide (N2O) -- 40. Propofol -- PART VIII: Hemostatic and Vasoactive Agents -- 41. Embolic Agents -- 42. Aspirin and Plavix/Clopidogrel -- 43. Warfarin (Coumadin) -- 44. Heparin -- 45. Tissue Plasminogen Activator (tPA) -- 46. Oxidized Cellulose -- 47. Nasal Decongestants -- PART IX: Cardiovascular Support Agents -- 48. Supplemental Oxygen -- 49. Hypertonic Saline -- 50. Mannitol (1,2,3,4,5,6-Hexanehexol) -- 51. Triple H Therapy -- 52. Angiotensin Converting Enzyme (ACE) Inhibitors -- 53. Acetazolamide (Diamox) -- 54. Amiodarone -- PART X: Anti-inflammatory Agents -- 55. Acetominophen (Tylenol, Paracetamol) -- 56. Natalizumab (Tysabri, Biogen IDEC and Elan Pharmaceuticals) -- 57. Synthetic Corticosteroids -- PART XI: Dietary Supplements, Homeostatic Agents, Hormone-like Drugs -- 58. Manganese in Total Parenteral Nutrition -- 59. Zinc Oxide (ZnO) -- 60. Insulin -- 61. Bisphosphonates -- 62. Recombinant Human Bone Morphogenetic Protein -- 63. Retinoids (13-cis-Retinoic Acid, Isotretinoin, Accutane, All-trans-retinoic acid) -- 64. Topical Prostaglandin Analogues -- 65. Oral Contraceptives (Estrogen and Progestin) -- 66. Fish Oil -- PART XII: Injectable Filler Agents -- 67. Calcium hydroxyapatite-based Fillers -- 68. Hyaluronic Acid-based Fillers -- 69. Injectable Silicone Oil.
Keywords: Radiology; Pharmacology; Radiology; Pharmacology; Neuroimaging; Brain -- drug effects; Spinal Cord -- drug effects; Drug-Related Side Effects and Adverse Reactions; Substance-Related Disorders; Tomography; Diagnosis, Differential